A priority framework for the development of a health care-associated infection surveillance program in Australian residential aged care homes: Analysis of a Delphi technique - Watson, Eliza; Worth, Leon J.; Thursky, Karin; Lim, Lyn-Li; Bull, Ann; Sluggett, Janet K.; Dunt, David; Bennett, Noleen (American journal of infection control, 2025)
There is no agreed scope for a comprehensive national residential aged care home (RACH) health care-associated infection (HAI) surveillance program in Australia. Three sequential surveys were anonymously and independently completed by 25 to 40 subject experts. Participants rated the importance and feasibility of including potential program elements in a national RACH HAI surveillance program using Likert scales. Aggregate agreement levels were defined as consensual (≥ 90%, surveys 2 and 3), high (≥ 75%, survey 1 or 75%-89%, surveys 2 and 3), moderate (31%-74%, all surveys), or low (≤ 30%, all surveys). Program elements were classified “priority 1” (if there was consensual agreement for importance and feasibility), 2, 3, or nonpriority. Of 58 potential program elements, 26 were classified as priority 1; this included program elements focused on infection surveillance (5), infection detection criteria (1), organism surveillance (8), isolate monitoring methods (1), vaccination compliance (4), vaccination compliance targets (4), and antimicrobial appropriateness measures (3). Six, 14, and 12 program elements were classified priority 2, 3, and nonpriority, respectively. Our study developed a strategic framework for a national RACH HAI surveillance program by determining priorities for inclusion of program elements. This framework will be used to develop a pilot program for Australian RACHs. •A Delphi technique was used to determined RACH HAI surveillance program elements.•Academic and clinical experts provided unbiased, equal input.•The experts found 26 elements both important and feasible for inclusion.•Priority elements will be used to develop a pilot program for Australian RACHs.